Analisis dan Perancangan Basis Data dan Aplikasi Pegadaian pada PT Langitan Segi Putera - Diana Diana (Bina Nusantara University, 2012)
This article contains analysis and design of pawnshop database systems and its application design that can be used by PT Langitan Segi Putera for acquiring information about pawn goods, decision making in pawnshop system, how to increase the effectiveness and efficiency of employee performance as well as how to reduce error in data input. The methodology used in this research consists of literature study, survey, and analysis and design. The result obtained is a conceptual, logical and physical database design for pawn process in PT Langitan Segi Putera and its application that is suitable with the design. The design of database and its application meets the company requirement and improves company performance due to the availability of accurate and timely information, improvement in data security, and reduction of data redundancy.